Primary School Students’ Experiences during Game Development Project Using Scratch - Siew Wan, Lee; Khalid, Fariza (International Journal of Engineering and Technology, 2018)
Scratch is one of the programming software that allows users to create their own interactive stories, games, and animation and sharing through online. This study aims to study students’ experiences during their involvement in game development using Scratch. Research participants were 30 years six primary school students from one of the Chinese primary schools in Kuala Lumpur. This study employed a qualitative research design through which in-depth interviews were conducted to gain answers to how their participation in game development activity using Scratch helped them develop problem-solving skills. Data were analyzed using a thematic analysis. Based on the analysis, it was revealed that the activity of games development using Scratch has impacted how students solve their problems. It was also reported that students valued their games development activity as something that is fun but challenging. Participants also cited feeling more interested in learning about Scratch after this project. This paper also discusses the potential of computational thinking skills in enhancing students’ ability in creating more creative and fruitful projects.